PENGARUH SERVICES QUALITY DAN KENYAMANAN TERHADAP KEPERCAYAAN GUNA MENINGKATKAN KEPUASAN KONSUMEN PADA MOBIL TRAVEL (MMI) MUKO-MUKO INDAH TRAVEL. (STUDI KASUS PENUMPANG TRAVEL MMI DI KOTA BENGKULU) - Yumita, Aulia Tasya (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2023)
Research on Mukomuko Indah Travel Travel Cars (MMI) with the formulation of the problem How does service quality and comfort affect trust in order to increase consumer satisfaction in MMI travel cars? The population used in this study were all consumers on the MMI Travel Car totaling 100 respondents. The sampling technique used accidental sampling based on predetermined criteria totaling 100 respondents. Based on the results of research that has been done about the effect of Service Quality, Convenience, on Trust in order to increase Consumer Satisfaction in using MMI Services it can be concluded as follows: Service Quality affects trust in using services. Convenience affects trust in using services. Trust affects consumer satisfaction in using services. Service Quality has an indirect effect on consumer satisfaction in using services. Convenience has an indirect effect on consumer satisfaction in using services. Trust in Customer Satisfaction of MMI Passengers positive and significant influence between Service Quality on Consumer Satisfaction Keywords :  Service Quality, Convenience, Trust, Consumer Satisfaction.